THE IMPACT OF HYBRID WORK ARRANGEMENT SWITCHING INTENSITY ON DAILY WELL-BEING AND WORK OUTCOMES: THE MODERATING ROLE OF WORK CHARACTERISTICS - Chappell, Josh Matthew (University of Oklahoma – Graduate College, 2026)
As hybrid work becomes more common, employees frequently switch between working from home (WFH) and at the office (WATO). This study introduces a novel concept known as Hybrid Work Arrangement Switching Intensity (HWASI), which is the frequency of these transitions. Drawing on Cognitive Load Theory as well as Job Demands-Resources theory, the current study posited that such switching depletes employee energy and thus increases exhaustion and reduces vitality, which in turn predict next-day outcomes such as performance, job satisfaction, and emotional states. Using a 10-day experience sampling methodology (ESM), this study empirically examined associations between HWASI, daily energy levels, and work outcomes. We also investigated whether work characteristics (e.g., task complexity) moderated the association between HWASI and energy levels. Findings indicate that HWASI was not a reliable indicator for energy levels or next-day outcomes although it did have an indirect effect on job satisfaction through exhaustion. Furthermore, post hoc analyses indicated that task switching and task complexity were positively related to exhaustion, while autonomy over work location was negatively related to exhaustion. Implications and future directions based on these findings are discussed.
Keywords: Occupational psychology; Psychology; Hybrid-Work; Job Demands-Resources; Occupational Health